Myeloablative I-131-Tositumomab with Escalating Doses of Fludarabine and Autologous Hematopoietic Transplantation for Adults Aged ≥ 60 Years with B-Cell Lymphoma - Gopal, Ajay K. (2014)
Myeloablative therapy and autologous stem cell transplant (ASCT) is underutilized in older patients with B-cell non-Hodgkin (B-NHL) lymphoma. We hypothesized that myeloablative doses of (131)I-tositumomab could be augmented by concurrent fludarabine based on preclinical data indicating synergy. Patients were ≥60 years of age, had high-risk, relapsed, or refractory B-NHL. Therapeutic infusions of (131)I-tositumomab were derived from individualized organ-specific absorbed dose estimates delivering ≤27Gy to critical organs. Fludarabine was initiated 72 hours later followed by ASCT to define the maximally tolerated dose. Thirty-six patients with a median age of 65 yrs (range 60–76), 2 (range 1–9) prior regimens, and 33% with chemoresistant disease were treated on this trial. Dose limiting organs included lung (30), kidney (4), and liver (2) with a median administered (131)I activity of 471 mCi (range 260–1620). Fludarabine was safely escalated to 30 mg/m(2) × 7 days. Engraftment was prompt, there were no early treatment-related deaths, and 2 patients had ≥ grade 4 non-hematologic toxicities. The estimated 3 yr overall survival, progression-free survival, and non-relapse mortality were 54%, 53%, and 7%, respectively (median follow up of 3.9 yrs). Fludarabine up to 210mg/m(2) can be safely delivered with myeloablative (131)I-tositumomab and ASCT in older adults with B-NHL.